MENINGKATKAN AKTIVITAS BELAJAR DAN HASIL BELAJAR IPA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DI KELAS IX-D SMP NEGERI 4 TANJUNG MORAWA - Eva Juniar Simamora (PGSD Universitas Negeri Medan, 2016)
The problem in this research is the poor result of student learning outcomes due to lack of student interest and the methods used by the teacher is not supporting it. The purpose of this study is determine student learning activity and to improve the outcomes of class IX-D SMP Negeri 4 Tanjung Morawa in the academic year 2015/2016 by using cooperative learning model STAD in solving the problem IPA. This study is a class act consisting of two cycles, each cycle comprises four activities: planning, action, observation and reflection,followed by planning the next cycle to take advantage of the man that is graders.Subject of this research are 36 students, they are 27 females and nine males all of them are grade IX. Key Words: Cooperative lerning Model STAD, IPA